Peripheral blood lymphocyte response to phytomitogens in systemic lupus erythematosus. Issue 5 (October 1976) - Foad, B.; Adams, L. E.; Litwin, A.; Hess, E. V.
Abstract : Foad, B., Adams, L. E., Litwin, A., and Hess, E. V. (1976). Annals of the Rheumatic Diseases, 35, 407-414. Peripheral blood lymphocyte response to phytomitogens in systemic lupus erythematosus. The response of peripheral blood lymphocytes to the phytomitogens, PHA, Con A, and PWM, was evaluated in 30 SLE patients and in 30 age, sex, and race-matched controls using dose and time responses. The proliferative response to the three phytomitogens was not depressed in this group of subacute and chronic SLE patients. Active lupus nephritis and a slow acetylator phenotype were associated with a decreased lymphocyte response. The incidence of a slow acetylator phenotype in spontaneous SLE was 68%. In interpreting the lymphocyte response to phytomitogens, the importance of a clear definition of the SLE group under study, the activity of the disease, and treatment status are emphasized.